THE ROLE OF BICYCLE TRANSPORT DEVELOPMENT IN IMPLEMENTING THE “GREEN MAKON” NATIONAL PROJECT (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
As part of this project, green spaces are being created in various cities, trees are being planted, and activities aimed at restoring the natural environment are being carried out. The "Green Makon" project is of great importance in supporting the development of cycling infrastructure, transforming cities into green spaces, and improving the ecological situation. This article addresses urgent issues related to enhancing the ecological environment and promoting the development of cycling transport.